Pengaruh Bobot Bibit Awal Yang Berbeda Terhadap Laju Pertumbuhan Rumput Laut Kappaphycus alvarezii Menggunakan Metode Rakit Apung - khaidir haidir; Rika Wulandari; Henky Irawan (Intek Akuakultur, 2021)
This study aimed to determine the best initial seedling weight in Kappaphycus alvarezii seaweed cultivation using the floating raft . This research was conducted for 52 days, starting from May to June 2021, in Berakit Village, Riau Islands. The method used was Completely Randomized Design (CRD) with 3 treatments and 3 replications, Treatment A (Seed weight 50 g), Treatment B (Seed weight 100 g) and Treatment C (Seed weight 150 g). The results of the study after the statistical test of variance ANOVA, the effect of different seed weights on the growth rate of Kappaphycus alvarezii seaweed Using the floating raft method showed significantly different results on the growth rate of seaweed (P<0.05). The results obtained were Absolute Weight (g) Treatment 50 g (263.71 ± 26.25 g), B (414.94 ± 14.51 g) and C (512.59 ± 32.88 g). Absolute Growth (g) Treatments A (213.70 ± 26.25 g), B (314.95 ± 14.51 g) and C (407.78 ± 31.69 g). Specific Growth Rate (%) Treatment A (5.09 ± 0.62 %/day), B (7.50 ± 0.35 %/day) and C (8.63 ± 0.78%/day). Survival rates in treatments A, B, and C Levels 1 and 2 obtained the same or identical results (100±0.00).